Bulk-fill versus conventional composite: A comparative analysis on degree of conversion - De Albuquerque Jassé, Fernanda Ferreira (2019)
Aim: This study aimed to determine the degree of conversion (DC) of two resin-based composites: A conventional nanohybrid composite and a bulk-fill flowable composite (SureFil® SDR™ flow). Materials and Methods: DC was evaluated at 1-, 2-, 3-, and 4-mm depths at varying irradiation times (20 and 40 s) by Fourier-transform infrared spectroscopy. Disc-shaped specimens of varying depths were prepared and photoactivated with a third-generation light-emitting diode light-curing unit. The specimens were stored for 24 h in the dark at ambient temperature and pulverized into a fine powder which was mixed with potassium bromide. After homogenization, the mixture pressed to form a pellet. All pellets were evaluated by an infrared spectrometer equipped with a triglycine sulfate detector using diffuse reflectance. The percentage of monomer conversion was determined from the ratio of the absorbance intensities of the aliphatic carbon-carbon double bonds (C = C) and the internal standard before and after the curing of the composite, represented by the aromatic carbon-carbon single bonds (C-C). Results: The DC data for the bulk-fill resin showed no significant difference (P > 0.05) for different irradiation depths, whereas for the conventional nanohybrid resins, statistical analyses revealed a significant result of the variables time and depth as well as the interaction between them. Conclusions: The results indicated that SDR™ achieves a 4-mm depth of cure with both 20- A nd 40-s light exposures.